Peran Media Lokal dalam Kebencanaan: Analisis Framing Pemberitaan tentang Banjir di Ponorogo - Dwi Anggoro, Ayub; Lestarini, Niken; Pinaryo (Universitas Muhammdiyah Yogyakarta, 2025)
This research analyzes the role of local media in a disaster context by examining the construction of reality in flood reporting in Ponorogo by the Local Media